The association between dietary fat intake and benign breast diseases: a systematic review - Amir Hossein Faghfouri; Fatemeh Azizi-Soleiman; Sevda Saleh-Ghadimi; Hamed Jafari-Vayghan (Clinical Nutrition Open Science)
Summary: Benign breast diseases (BBDs) may herald breast cancer, and diet is one of the most important environmental factors associated with both conditions. Dietary fat intake has been suggested as a potential risk factor for BBDs. We performed a systematic review to comprehensively scrutinize the current knowledge regarding the relationship between dietary fat intake (DFI), the types of consumed fats, and BBDs. A deep and meticulous search was conducted to gather relevant publications until 30th December 2023. The search was conducted in the following databases: PubMed/Medline, Web of Science, Embase, and Scopus. Eligible studies included female participants with BBDs, employed cross-sectional, case-control, or cohort designs, assessed dietary fat intake using validated tools, and reported outcomes as odds ratios, relative risk, or hazard ratios. After screening, a total of nine studies were included in our final review. The data required were extracted, and the risk of bias was assessed. Our systematic review found that the consumption of vegetable fat could be protective against BBDs while the consumption of animal fat and monounsaturated fat was associated with a higher risk of BBDs. No significant relationship was found between the intake of saturated and polyunsaturated fats and BBDs. A robust relationship between the consumption of various types of dietary fats and BBDs could not be elucidated based on available evidence. Nevertheless, it is advisable for patients who are at risk of BBDs to follow healthy eating habits and be vigilant about the excessive consumption of fats and oils.